A way to macroporous and alveolar geopolymer foams elaboration: Influence of operating parameters on porosity characteristics - S. Benkhirat; G. Plantard; E. Ribeiro; H. Glenat; Y. Gorand; K. Nouneh (Results in Materials)
Alveolar cellular foams are widely used in a wide range of applications, from aeronautics and filtration systems to chemical and transformation processes. Their porous characteristics make them a prime candidate for reactions, radiative transfer and flow. Geopolymeric foams, which have their origins in civil engineering, are materials with promising potential in terms of mechanical, thermal and acoustic resistance. As they are mainly used in civil engineering, the structures currently being developed are mainly closed-pore matrices. However, if they are to invert the field of photocatalytic oxidation processes, solar collectors or concentrated solar power plants, the supports need to develop a high exchange surface area. Metal alveolar foams have been identified as ideal but very costly supports. Geopolymeric foams could meet these requirements, but their surface areas are currently too limited for photoreactors. In this study, it is proposed to develop and optimize the operating conditions for geopolymer foam synthesis in order to impart macroporous properties and an interconnected alveolar structure. Based on two well-established synthesis methods (direct foaming and replication), operating conditions such as foaming agent and surfactant content, and drying and calcination conditions, are studied. Geopolymer foams are produced with different macroporous characteristics. We aim to define the synthesis conditions required to produce interconnected macroporous alveolar foams with milimetric pores. In civil engineering, these materials have the advantage of being easy to design, use and shape according to the application.